2022
DOI: 10.1155/2022/1629813
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus spp. Fermented Plant Protein Mix as a Potential Fishmeal Substitute in the Diet of Penaeus monodon: Emphasis on Nitrogen Metabolism

Abstract: A feeding experiment (60 days) was conducted to evaluate the effect of Bacillus spp. fermented plant protein mix in Penaeus monodon. A control diet (CNT) contains 25% fishmeal, of which 50% was substituted (w/w) with Bacillus spp. fermented plant protein mix at two different concentrations of 0.25 and 0.50% (PP-0.25 and PP-0.50, respectively), while the diet prepared with untreated ingredients served as a negative control (PP-0). The daily growth coefficient (DGC) did not differ in the groups fed CNT, PP-0.25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similar observations were reported by Gomes et al 69 in certain aquatic species reared with a semi-purified diet containing a higher content of rapeseed meal. Rajaram 49 could not able to include more than 2.5% of rapeseed meal in the diet of P. monodon, which was later confirmed by Jannathulla et al 70 in P. vannamei, which is mainly due to the presence of glucosinolates. Chiang et al 71 and Jannathulla et al 70 reported that the activity of protease increased from 200 U/g (Day 1)…”
Section: Effect On Antinutrientsmentioning
confidence: 91%
See 3 more Smart Citations
“…Similar observations were reported by Gomes et al 69 in certain aquatic species reared with a semi-purified diet containing a higher content of rapeseed meal. Rajaram 49 could not able to include more than 2.5% of rapeseed meal in the diet of P. monodon, which was later confirmed by Jannathulla et al 70 in P. vannamei, which is mainly due to the presence of glucosinolates. Chiang et al 71 and Jannathulla et al 70 reported that the activity of protease increased from 200 U/g (Day 1)…”
Section: Effect On Antinutrientsmentioning
confidence: 91%
“…monodon and P . vannamei , respectively 49,50 . Additionally, palatability issues persisted with tannin that could cause feed intake to drop, which would have an adverse effect on growth.…”
Section: Beneficial Effects Of a Nigermentioning
confidence: 99%
See 2 more Smart Citations